Pancreatic cancer - Friess, Helmut; Scheufele, Florian (Translational Gastroenterology and Hepatology; Vol 5 (July 2020): Translational Gastroenterology and Hepatology, 2020)
Malignant tumors of the pancreas—mainly pancreatic ductal adenocarcinoma (PDAC)—display a significant cancer burden to the population with an incidence of ~12.1/100,000 and a mortality of ~11.1/100,000 (1). In the Western world and in Germany, PDAC is currently ranked fourth place for causing cancer-related deaths (1,2). Furthermore, due to the increasing prevalence of PDAC and the stagnation in treatment strategies, PDAC is expected to reach rank two of cancer-related deaths by the year of 2030 (2).